„Vječne vode“ Stanislava Prepreka - Blažetin, Stjepan (SlavVaria, 2026)
Eternal waters by Stanislav Preprek. Stanislav Preprek’s poetry was completely unknown for the literary public until 2004. when his poems were published posthumously into Serbian language under the title Pred tminama (Before darkness). Last year, on the occasion of the 20th anniversary of his death the Institute for Culture of the Croatians in Vojvodina published all of Preprek’s works, including the poems in Croatian language, which language they had been originally written in. Preprek wrote poems all his life. He wrote 346 poems from which only one was published in his lifetime. This paper discusses the motif of water or water in the poetry of Stanislav Preprek.